CHEMICAL CHARACTERISTICS AND FIBER FRACTION OF RUMINANT COMPLETE FEED BASED ON SEAWEED (PADINA AUSTRALIS) WITH DIFFERENT LEVELS OF USE - Irmayanti, Irmayanti; Palayukan, Jisril; Suriansyah, Suriansyah (Fakultas Peternakan, Universitas Padjadjaran, 2025)
The aim of this study was to examine the effect of the level of seaweed (Padina australis) as a ruminant feed on the nutritional quality and fiber fraction of complete diets. The variables observed were dry matter, crude protein, crude fiber, crude fat, extract material without nitrogen, ash content, acid detergent fiber and neutral detergent fiber. This study was based on a completely randomized design (CRD) with 4 treatments and 4 replications, namely P0 = complete feed (control), P10 = complete feed with 10% Padina australis level, P20 = complete feed with 20% Padina australis level, and P30 = complete feed with 30% Padina australis level. The results showed that the use of Padina australis up to 30% can increase dry matter, crude protein and reduce crude fiber, crude fat and ash content as well as neutral detergent fiber and acid detergent fiber content. The use of Padina australis at 20% level is the best treatment because it can reduce crude fat 6.21%, ash content 16.56%, neutral detergent fiber 50.88% and acid detergent fiber 31.22%.